FORMATION PROBLEMS OF COMPETENCES OF THE DIGITAL ECONOMY - N. Unizhayev (Publishing House of the State University of Management, 2018)
The main problems of introducing disciplines that form competencies of the digital economy in the education process have revealed, the ways of solution have proposed. As a hypothesis, main reasons are the low proportion of faculty members, who retrained to form competencies of the digital economy and the lack of mechanisms for selection promising research areas and development in the field of digital technologies. Removal of causes will allow receiving a system effect and triggering off a multitude innovation economic processes.